PHYTOCHEMICAL ANALYSIS, IN VITRO ANTIOXIDANT POTENTIAL AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY STUDIES OF DICRANOPTERIS LINEARIS - Rajesh, Kalpana Devi; Vasantha, Subramani; Panneerselvam, Annamalai; Valsala Rajesh, Nakulan; Jeyathilakan, Narayanaperumal (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of the study was to analyze qualitative and quantitative phytochemicals, evaluate in vitro antioxidant properties and determine the bioactive compounds in extracts of Dicranopteris linearis (Burm.f.) Underw. collected from Western Ghats of Kanyakumari district. Methods: The qualitative, quantitative phytochemical, and in vitro antioxidant analysis were performed using standard procedures. The bioactive compounds were analyzed using gas chromatography-mass spectrometry (GC-MS) instrument. Results: The qualitative phytochemical analysis studied in aqueous, acetone, chloroform, ethanol, and petroleum ether solvent extract showed acetone had strong positivity to express the 12 phytoconstituents studied except anthocyanin when compared to other solvent extracts. The quantitative phytochemistry revealed considerable amount of terpenoids (97.0±1.15 mg/g), tannins (30.8±0.44 mg tannic acid equivalents/gram), phenols (28.6±0.33 mg gallic acid equivalents/gram), and flavonoids (8.50±0.29 mg quercetin equivalent/g) in decreasing order of concentrations. The in vitro antioxidant activity of aqueous, ethanol, acetone, chloroform, and petroleum ether suggested that the extract of DL has prominent antioxidant prospective against various free radicals such as 2,2-diphenyl-1-picrylhydrazyl while butylated hydroxy toluene being the standard antioxidant used. The GC-MS analysis displayed the presence of 11 bioactive compounds each belonging to various categories of phytochemicals such as terpenoids, flavonoids, phenols, and fatty acid derivatives. Conclusion: The results indicate that D. linearis (Burm.f.) Underw. present in the Western Ghats of Kanyakumari is an effective scavenger of free radicals and has the potential to be used as a natural antioxidant which is attributed to the rich presence of secondary metabolites. Keywords: Dicranopteris linearis (Burm.f.) Underw., Phytochemistry, Antioxidant activity, Gas chromatography-mass Spectrometry.